How doctors think : clinical judgment and the practice of medicine - Montgomery, Kathryn, 1939- (Oxford University Press, 2006)
"How Doctors Think" defines the nature and importance of clinical judgement. Although physicians make use of science, this book argues that medicine is not itself a science, but rather an interpretive practice that relies on clinical reasoning. A physician looks at the patient's history along with the presenting physical signs and symptoms, and juxtaposes these with clinical experience and empirical studies to construct a tentative account of the illness. "How Doctors Think" is divided into four parts. Part One introduces the concept of medicine as a practice rather than a science; Part Two discusses the idea of causation; Part Three delves into the process of forming clinical judgement; and Part Four considers clinical judgement within the uncertain nature of medicine itself. "How Doctors Think" contends that there can be adverse side effects to assuming that medicine is strictly science, and suggests reducing these by recognizing the vital role of clinical judgement.